Alirocumab as add-on therapy to statins: current evidence and clinical potential. (July 2018) - Auer, Johann; Berent, Robert
Atherosclerotic cardiovascular diseases (ASCVDs) are associated with a substantial mortality, physical morbidity, and mental disability. Elevated plasma low-density lipoprotein cholesterol (LDL-C) levels play a major role in the pathophysiology of ASCVDs. Statins have been shown to reduce ASCVD risk and associated events and are recommended as first-line therapy for treatment of hypercholesterolemia by current international guidelines. The key issue is to attain guideline-recommended LDL-C levels (below 70 mg/dl) for patients at very high cardiovascular risk. However, many high-risk and very-high-risk patients on statin therapy remain beyond treatment goals despite lifestyle modification and statins, and are exposed to a high risk of future cardiovascular events including myocardial infarction (MI), stroke, revascularization procedures, and death. This clearly emphasizes the urgent need for additional LDL-C reduction with new therapeutic strategies to target these highly atherogenic particles and to further reduce the burden of ASCVDs. Proprotein convertase subtilisin/kexin type 9 (PCSK9) plays a major role as a key regulator of the hepatic LDL receptor recycling process. Developments over the past 15 years have demonstrated PCSK9 inhibition to be a novel therapeutic strategy to manage increased LDL-C levels. A number of clinical studies using humanized monoclonal antibody technology against PCSK9 have shown profound reductions of LDL-C levels when used either alone or in combination with statin therapy. Recently, the first cardiovascular outcome study demonstrated a significant reduction of ASCV events when evolocumab was added to a statin therapy. This review will discuss current knowledge about antibody-mediated PCSK9 inhibition as add-on therapy to statin and the clinical potential that may be expected.